1.Zapisz każdą z podanych sum na dwa inne sposoby, zmieniając kolejnosc wyrazów :
a)x-2y+5 =
b)-a + 3b + 8 - 7c =
c)5k-2l-3m + 9=
2.a)3x+4x+5y-2y=
b)2a-3a+7-6=
c)2x-5x+7-6 =
d)2a+b-4b =
e)x-2x+3+x-4 =
f)3x-y+4x-2y=
g)2x-6+4x+2=
h)3y-5-5y-6=
i)-2a+2a-3a-3b=
j)1/2t-2x+3t-x-t=

2

Odpowiedzi

2010-03-23T19:13:08+01:00
A)x-2y+5 =-2y+x+5
b)-a + 3b + 8 - 7c = 3b - a + 8 - 7c
c)5k-2l-3m + 9= 3h+2k-2l-3m+3*3
2.a)3x+4x+5y-2y= 7x+3y
b)2a-3a+7-6=1-a
c)2x-5x+7-6 = 1-3x
d)2a+b-4b = 2a+3b
e)x-2x+3+x-4 = -1
f)3x-y+4x-2y= 7x-3y
g)2x-6+4x+2=6x-4
h)3y-5-5y-6=-11-2y
i)-2a+2a-3a-3b= -3a-3b
j)1/2t-2x+3t-x-t= 2 1/2t - 3x
2010-03-23T19:16:41+01:00
1.
a) 5+2y-x= 5+(2y-x)=
b)(-a+3b)+8-7c= (-a+3b)+(8-7c)=
c)-3x+7-6= (2x-5x)+(7-6)=
d)2a+(-1)+4+x=2a-(-1)+4+x=2a+5+x=
masz dalej mi się nie chce